Education Leaders’ Perception on the Effectiveness of Online Learning during the COVID -19 Crises in UAE Universities - Abuhmaid, Atef; Jarrah, Hani (Nurture, 2022)
Purpose: The current study aimed at exploring education leaders’ perceptions of online learning in four universities in the United Arab Emirates’ (UAE) during the COVID-19 pandemic crisis. The study explored two dimensions of educational institutions’ experiences during the pandemic: the effectiveness and educational impact of online learning. Design/Methodology/Approach: To achieve the aim of the study, a 34-items survey was developed. The validity and reliability of the survey were ensured. A total of 113 education leaders across five UAE universities were surveyed in order to know their views on the effectiveness of online teaching during COVID-19 lockdowns. Findings: The results of the study showed that despite the pressure, stress and uncertainty that accompanied the shift to online education as a result of the spread of coronavirus. University education leaders highly appreciated online teaching in both domains of the survey. However, the more experienced education leaders expressed positive views on the effectiveness of online learning during the COVID-19 pandemic. At the same time, there were no significant differences in perceptions among education leaders based on gender, academic rank or position. Conclusion: The current study explored education leaders’ views on online learning. Apparently, addressing differences among education leaders can help in providing more effective and sound learning experiences. Practical implications: The results of the study highlighted the crucial role of education leaders especially during times of crises and massive disruptions and the need to take into account the differences between their views. Therefore, the study suggests dealing with education leaders’ differences carefully in order to deliver effective online learning. Contribution to literature: The study provides a different perspective on online learning as it captures education leaders’ perspectives on online learning during the COVID-19 pandemic.